Exploring the role of adult attachment, major depression and childhood trauma in arterial stiffness: A preliminary study - SAKALLI KANİ, AYŞE; ÇİNÇİN, AHMET ALTUĞ; ÖZERCAN, AHMET; TOPÇUOĞLU, VOLKAN; SAYAR, MUSTAFA KEMAL (My University, 2023)
Objective: Prior research indicates a noteworthy and intricate connection between depression and subclinical atherosclerosis. Nevertheless, the biological and psychological mechanisms that underlie this association are not yet fully understood. To address this gap, this exploratory study aimed to examine the relationship between active clinical depression and arterial stiffness (AS), with a particular focus on the potential mediating roles of attachment security and childhood trauma. Methods: In this cross-sectional study, we examined 38 patients with active major depression free of dyslipidemia, diabetes mellitus, hypertension, and obesity and 32 healthy controls. All participants underwent blood tests, psychometric assessments, and AS measurements using the Mobil-O-Graph arteriograph system. AS severity was evaluated using an augmentation index (AIx) normalized to 75 beats/min. Results: In the absence of defined clinical cardiovascular risk factors, there was no significant difference in AIx between individuals with depression and healthy controls (p = .75). Patients with longer intervals between depressive episodes had lower AIx (r = −0.44, p < .01). Insecure attachment and childhood trauma did not significantly associate with AIx in patients. Whereas insecure attachment was positively correlated with AIx only in healthy controls (r = 0.50, p = 01). Conclusions: Our analysis of established risk factors for atherosclerosis revealed that depression and childhood trauma had no significant relationship with AS. However, we did identify a novel finding: insecure attachment was significantly associated with AS severity in healthy adults without defined cardiovascular risk factors for the first time. To our knowledge, this is the first study to demonstrate this relationship.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Klinik Psikolojisi; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Clinical Psychology; Health Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Psikiyatri; PSİKOLOJİ, KLİNİK; Clinical Medicine (MED); Natural Sciences (SCI); PSYCHIATRY; PSYCHOLOGY; PSYCHOLOGY, CLINICAL; Klinik Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psikiyatri ve Ruh Sağlığı; Social Sciences & Humanities; Psychiatry and Mental Health; Arterial stiffness; Attachment; Childhood trauma; Depression